Tuberculosis Control in Ecuador: Unforeseen Problems, Unanticipated Strengths - Stan Houston (Canadian Respiratory Journal)
Ecuador is among the eight countries with the highest tuberculosis (TB) prevalences in the Americas (the World Health Organization estimates 141 new cases/100,000 population in 2002) and has had a poorly functioning TB control program. As described in an earlier editorial (1), the Canadian Lung Association, with funding from the Canadian International Development Agency, has been involved for four years in supporting Ecuador?s National TB Program. The initial phase of the project has just been completed, but the experience has already provided many valuable lessons, some quite unexpected.